Differences in Hospital Readmission Risk across All Payer Groups in South Carolina. (28th September 2016) - Chakraborty, Hrishikesh; Axon, Robert Neal; Brittingham, Jordan; Lyons, Genevieve Ray; Cole, Laura; Turley, Christine B.
Abstract : Objective: To evaluate differences in hospital readmission risk across all payers in South Carolina (SC). Data Sources/Study Setting: South Carolina Revenue and Fiscal Affairs Office (SCRFA) statewide all payer claims database including 2, 476, 431 hospitalizations in SC acute care hospitals between 2008 and 2014. Study Design: We compared the odds of unplanned all‐cause 30‐day readmission for private insurance, Medicare, Medicaid, uninsured, and other payers and examined interaction effects between payer and index admission characteristics using generalized estimating equations. Data Collection: SCRFA receives claims and administrative health care data from all SC health care facilities in accordance with SC state law. Principal Findings: Odds of readmission were lower for females compared to males in private, Medicare, and Medicaid payers. African Americans had higher odds of readmission compared to whites across private insurance, Medicare, and Medicaid, but they had lower odds among the uninsured. Longer length of stay had the strongest association with readmission for private and other payers, whereas an increased number of comorbidities related to the highest readmission odds within Medicaid. Conclusions: Associations between index admission characteristics and readmission likelihood varied significantly with payer. Findings should guide the development of payer‐specific quality improvement programs.